Practitioner Perspective: an analysis of Intensive English Language Program Curriculum Reform in a Federal Higher Education Institution in the UAE - Alnuaimi, Haya (2021)
Curriculum development is considered to be the core of the Education sector. Therefore, examining and evaluating the curriculum content and development process has been a continuing concern among researchers in the educational field. Hence, this research aims to analyse and assess the level 2 curriculum reform of the Intensive English Language Program (IELP) in a federal higher education institution in the UAE. To achieve the aim of the research, two objectives were designated: evaluating the appropriateness of the intensive English language program curriculum reform, and providing recommendation based on the literature and own experience for further development. A number of findings/conclusions were made through analysing the IELP level 2 curriculum. The first conclusion is that curriculum developers in this institution followed the National Curriculum Model and Tyler’s Model in planning, implementing and evaluating the curriculum. Furthermore, the analysis of the curriculum components also showed that the IELP curriculum was following the Common European Framework of Reference for Languages (CEFR). CEFR played an important role in determining students’ level and understanding their needs. Another conclusion from the analysing of the IELP level 2 curriculum is that the time designated for each cycle is not enough for achieving all the learning outcomes mentioned in the curriculum. These findings provide an insight for further development of the IELP and future research to understand the IELP. It is recommended that future research should consider conducting surveys and interviews with different curriculum stakeholders, especially those most affected by it, that is, students, teachers and parents. It is argued that surveys and interviews will provide better understanding of the curriculum development and the impact of the IELP curriculum on both teachers’ well-being and students’ language proficiency and well-being.